The effect of sprint interval training on key cardiometabolic risk factors in children and adolescents: a systematic review and meta-analysis - Liang, Weibao; Dai, Jianmin; Liu, Chuannan; Yan, Xujie; Xu, Shuting; Huang, Wenbai (Frontiers in Physiology, 2025)
BackgroundAlthough sprint interval training (SIT) is a time-efficient modality known to improve adult cardiometabolic health, a comprehensive synthesis of its effects in pediatric populations is lacking.ObjectiveThis systematic review and meta-analysis evaluated the impact of SIT on key cardiometabolic risk factors in children and adolescents.MethodsSix electronic databases were searched for trials comparing SIT against non-exercising control (CON) or moderate-intensity continuous training (MICT). A random-effects model was used to compute the standardized mean difference (SMD). The study quality and evidence certainty were assessed using the Cochrane RoB 2 and GRADE frameworks, respectively.ResultsFourteen studies with 467 participants were included. Compared to CON, SIT elicited a large, significant improvement in cardiorespiratory fitness (VO2max) (number of studies, k = 12; SMD = 1.43, p = 0.004) based on evidence of moderate certainty. Significant improvements in body composition were also observed, including a large reduction in the body fat percentage (k = 7; SMD = −0.83, p = 0.012), a moderate reduction in waist circumference (k = 9; SMD = −0.69, p = 0.006), and a small reduction in body weight (k = 12; SMD = −0.15, p = 0.020). In contrast, SIT had no significant effects on the blood lipids, glycemic control parameters, or blood pressure (low to very low certainty evidence). Direct comparisons between SIT and MICT revealed no significant differences for any outcome.ConclusionSIT is an effective strategy for enhancing cardiorespiratory fitness and improving body composition in children and adolescents. With an efficacy comparable to that of traditional MICT, it represents a viable, time-efficient exercise alternative for pediatric populations.Systematic Review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251131717, identifier CRD420251131717.